PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWER POINT ISPRING SUITE 8 DI SEKOLAH DASAR - Imam Nuraini; Sutama Sutama; sabar narimo (Jurnal VARIDIKA, 2019)
The purpose of this research is to develop learning media using power point I Spring Suite 8 which are valid, practical and effective on the concept of the Central and Local Government Systems. The method used is development research with reference to the ADDIE development model which consists of 5 stages: analysis, design, development, implementation, and evaluation. The assessment instruments consisted of three, namely (1) validity instruments in the form of validity assessment tools of interactive learning media Power Point Ispring Suite 8 and validity assessment instruments questionnaire, (2) practicality instruments in the form of teacher responses and students' responses to learning media using Power Point Ispring Suite 8, and (3) effectiveness instruments in the form of student learning outcomes. Based on data analysis, obtained an average of media validity is 4.15 (valid). Practicality of the media obtained 93.40% teacher response (very strong) and student responses of 91.40% (very strong). Learning Media has fulfilled the effectiveness criteria, namely 91% of students achieve mastery learning value. Based on the results of the study it can be concluded that the learning media based on Power Point Ispring Suite 8 on the concept of central and regional government that is developed is valid, practical, and effective.